THE ROLE OF LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION AT THE ISLAMIC BOARDING SCHOOL - Poppy Rachman (At- Ta'lim : Jurnal Pendidikan, 2022)
This paper aims to review the leadership and improvement of education quality in Islamic boarding schools. To realize the objectives of boarding school, a leader who has the ability to answer various challenges, has a vision to come to the excellent boarding school, and the effort to achieve it with high energy and commitment. Leaders who always try to influence their subordinates through direct communication by emphasizing the importance of values, assumptions, commitments, and beliefs and have a determination to achieve the goals. Leaders act in a way to motivate and inspire subordinates through the giving of meaning and challenge to the duties of subordinates. The meaning of the quality of education is the suitability of the needs in education which one means to improve the quality of human resources as well as to produce changing of humans to become a perfect human beings with the noble character and good personality.